Ecological Momentary Assessment in Patients With an Acquired Brain Injury: A Pilot Study on Compliance and Fluctuations - Forster, Saskia D.; Gauggel, Siegfried; Petershofer, Axel; Völzke, Volker; Mainz, Verena (Frontiers in Neurology, 2020)
Ecological Momentary Assessment (EMA) promises to be a suitable method for capturing the dynamics in self-assessments through repeated measurements in naturalistic environments using common mobile devices. Therefore, EMA could increase the power of neuropsychological assessment by obtaining a more fine-grained picture of symptoms, limitations, and strengths in patients with an acquired brain injury (ABI) in real-life situations. The present study examined 15 patients with an ABI with cognitive and motor impairments. Following a semi-randomized high-frequency sampling plan to assess EMA’s feasibility and applicability, data were collected across seven days. At eight prompts per day, patients were asked about their current activities, the social context they were in, their current mood, performance judgments of their own functional status, and the frequency of self-reflections. The average compliance rate was 71.6%. The fluctuations in patients’ responses were measured in terms of variance distributions within simple (intercept only) three-level models and root mean square of successive difference (rMSSD) values. They were sufficient, as shown for example by the mean within-person-variability of 44.9% across all of the items studied. There were no significant correlations between patients’ age, severity of depressive symptoms, or their level of functioning and their compliance with study participation or the variability of their responses. The results support the feasibility and applicability of EMA as an assessment technique in patients with an ABI. There are, however, limitations that should be considered when planning an assessment of brain-injured patients using EMA.